PERAN KELEMBAGAAN ADAT DALAM MEWUJUDKAN KEDAULATAN PANGAN - Rai Sita (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2012)
Problems of development currently face a critical developmental stage which is related to how humans attempt to continue the development and bequeath a decent life for the survival of future generations (sustainable development). Development leading to the modernization and globalization tends to be exploitative and impacts on food insecurity considering the increasing number of humans, yet the environmental damage is also increasing due to the imbalanced construction. It is indigenous community of Kasepuhan Sinar Resmi that still upholds traditional values ​​underlying the whole system of social life. Indigenous community Kasepuhan Sinar Resmi has a life philosophy of Earth Mother, Sky Father, Land of the Queen. The philosophy of life underlies the system of indigenous community. Economic life of the community is integrated to the cultural values ​​followed. Economic system that is run based on the custom value is able to bring the community to meet the need of food independently, so this is said to ably achieve food sovereignty. Keywords: Indigenous community, livelihood systems, food sovereignty